Torsin ATPases: Harnessing Dynamic Instability for Function - Chase, Anna R.; Laudermilch, Ethan; Schlieker, Christian (Frontiers in Molecular Biosciences, 2017)
Torsins are essential, disease-relevant AAA+ (ATPases associated with various cellular activities) proteins residing in the endoplasmic reticulum and perinuclear space, where they are implicated in a variety of cellular functions. Recently, new structural and functional details about Torsins have emerged that will have a profound influence on unraveling the precise mechanistic details of their yet-unknown mode of action in the cell. While Torsins are phylogenetically related to Clp/HSP100 proteins, they exhibit comparatively weak ATPase activities, which are tightly controlled by virtue of an active site complementation through accessory cofactors. This control mechanism is offset by a TorsinA mutation implicated in the severe movement disorder DYT1 dystonia, suggesting a critical role for the functional Torsin-cofactor interplay in vivo. Notably, TorsinA lacks aromatic pore loops that are both conserved and critical for the processive unfolding activity of Clp/HSP100 proteins. Based on these distinctive yet defining features, we discuss how the apparent dynamic nature of the Torsin-cofactor system can inform emerging models and hypotheses for Torsin complex formation and function. Specifically, we propose that the dynamic assembly and disassembly of the Torsin/cofactor system is a critical property that is required for Torsins’ functional roles in nuclear trafficking and nuclear pore complex assembly or homeostasis that merit further exploration. Insights obtained from these future studies will be a valuable addition to our understanding of disease etiology of DYT1 dystonia.